Crisis and continuity : time in the Gospel of Mark - Schildgen, Brenda Deen, 1942- (Journal for the study of the New Testament. Supplement series ;, 1998)
Here is a compact study of how Mark's Gospel meditates on time. It examines how the Gospel's contemporary setting in ordinary time defines its genre, and how Mark uses the Hebrew scriptures to remember and recall past teachings, prophecies and histories. The suspended time narratives, Mark's 'intercalations', on the other hand, interrupt the narrative of the critical time present. Finally, by bringing the eternal horizon into the events of the present, Mark's 'mythic time' reveals the crisis events as a momentary interruption of ordinary time. Similarly, during the 'ritual time', the Gospel na.